In the Flesh - Costa, Portia Da (Australia Harlequin Spice Publishers, 2012)
Posing nude to appease her now ex-fiance perhaps wasnt the most prudent idea Beatrice eatherly has ever had. With the photographs scrutinised up and down the ton and her brother running them into debt, Beatrice's hopes of making a respectable marriage are dashed. After one glance at Beatrices infamous racy cabinet cards, wealthy powerful Edmund Ellsworth Ritchie is soon obsessed with Beatrice's voluptuous figure. His indecent proposal, one monthe of hedonistic servitudein exchange for enough money to pay her brother's debts, is one she can hardly refuse....back cover.
Keywords: Man-woman relationships -- Secrecy -- England--London